Trigonometry

Geometry Level 3

1 + sin α 1 sin α \large \sqrt{1+\sin \alpha }-\sqrt{1-\sin \alpha}

If α [ π 2 , π ] \alpha \in \left[ \dfrac{\pi}{2},\pi\right] , then find the value of the above expression.

2 cos α 2 2 \cos \frac{\alpha}{2} 2 sin α 2 2 \sin \frac{\alpha}{2} None of these choices

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Chew-Seong Cheong
Jun 14, 2016

Solution suggested by @Vighnesh Shenoy

1 + sin α 1 sin α = 1 + 2 sin α 2 cos α 2 1 2 sin α 2 cos α 2 = sin 2 α 2 + cos 2 α 2 + 2 sin α 2 cos α 2 sin 2 α 2 + cos 2 α 2 2 sin α 2 cos α 2 = ( sin α 2 + cos α 2 ) 2 ( sin α 2 cos α 2 ) 2 = sin α 2 + cos α 2 sin α 2 + cos α 2 = 2 cos α 2 \begin{aligned} \sqrt{1+\sin \alpha} - \sqrt{1- \sin \alpha} & = \sqrt{1+2\sin \frac \alpha 2 \cos \frac \alpha 2} - \sqrt{1 - 2 \sin \frac \alpha 2 \cos \frac \alpha 2} \\ & = \sqrt{\sin^2 \frac \alpha 2 + \cos^2 \frac \alpha 2+2 \sin \frac \alpha 2 \cos \frac \alpha 2} - \sqrt{\sin^2 \frac \alpha 2 + \cos^2 \frac \alpha 2 -2 \sin \frac \alpha 2 \cos \frac \alpha 2} \\ & = \sqrt{\left(\sin \frac \alpha 2 + \cos \frac \alpha 2\right)^2} - \sqrt{\left(\sin \frac \alpha 2 - \cos \frac \alpha 2\right)^2} \\ & = \sin \frac \alpha 2 + \cos \frac \alpha 2 - \sin \frac \alpha 2 + \cos \frac \alpha 2 \\ & = \boxed{2 \cos \dfrac \alpha 2} \end{aligned}


My solution

1 + sin α 1 sin α = 1 + 2 tan α 2 1 + tan 2 α 2 1 2 tan α 2 1 + tan 2 α 2 = tan 2 α 2 + 2 tan α 2 + 1 1 + tan 2 α 2 tan 2 α 2 2 tan α 2 + 1 1 + tan 2 α 2 = tan α 2 + 1 1 + tan 2 α 2 tan α 2 1 1 + tan 2 α 2 = 2 1 + tan 2 α 2 = 2 sec α 2 = 2 cos α 2 \begin{aligned} \sqrt{1+\sin \alpha} - \sqrt{1- \sin \alpha} & = \sqrt{1+\frac{2 \tan \frac \alpha 2}{1 + \tan^2 \frac \alpha 2}} - \sqrt{1-\frac{2 \tan \frac \alpha 2}{1 + \tan^2 \frac \alpha 2}} \\ & = \sqrt{\frac{\tan ^2 \frac \alpha 2 + 2 \tan \frac \alpha 2 + 1}{1 + \tan^2 \frac \alpha 2}} - \sqrt{\frac{\tan ^2 \frac \alpha 2 - 2 \tan \frac \alpha 2 + 1}{1 + \tan^2 \frac \alpha 2}} \\ & = \frac{\tan \frac \alpha 2 + 1}{\sqrt{1 + \tan^2 \frac \alpha 2}} - \frac{\tan \frac \alpha 2 - 1}{\sqrt{1 + \tan^2 \frac \alpha 2}} \\ & = \frac{2}{\sqrt{1 + \tan^2 \frac \alpha 2}} \\ & = \frac{2}{ \sec \frac \alpha 2} \\ & = \boxed{2 \cos \dfrac \alpha 2} \end{aligned}

Instead if converting to tan one could directly use,
1 ± sin ( α ) = sin ( α 2 ) ± cos ( α 2 ) \sqrt{1 \pm \sin(\alpha)} = \left|\sin\left(\dfrac{\alpha}{2}\right) \pm\cos\left(\dfrac{\alpha}{2}\right)\right|

Log in to reply

Good solution. I will present it for you.

Chew-Seong Cheong - 5 years ago

Did the same way +1!

Rishabh Tiwari - 5 years ago

Nice solution sir,+1!

Rishabh Tiwari - 5 years ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...